Peran Orang Tua Terhadap Kemampuan Literasi Dini Anak Di Desa Banturung Kecamatan Bukit Batu - Elisabeth Fransisca Saragi Sitio; Vitaloka Anggriani (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2022)
This research aims to determine the role of parents in children's early literacy skills in Banturung Village, Bukit Batu District. The research method is a quantitative descriptive method. The research was conducted by distributing questionnaires to parents. The research procedures were determining the research subjects, making research instruments, validating instruments in the form of questionnaires, testing questionnaires, giving questionnaires, processing research data, and drawing research conclusions. Researchers present the results of research related to the role of parents in early literacy skills of children aged 5-6 years in Banturung Village, Bukit Batu District. Data obtained from the results of a questionnaire 30 respondents. The questionnaire consists of 24 statement items that include indicators of the role of parents on children's early literacy skills, namely Modelling, Mentoring, Organizing, Teaching with sub indicators namely Print Motivation, Phonological Awareness, Vocabulary, Narrative Skill, Print Awareness and Letter Knowledge. The Modelling shows a percentage of 66.38% which is included in the high criteria. The Mentoring shows a percentage of 76.38% which is included in the high criteria. The Organizing shows a percentage of 71.80% which is included in the high criteria. Teaching shows a percentage of 71.52% is included in the high criteria. Based on the results of the questionnaire research as a whole, it can be concluded that 72.22% stated that the role of parents in early literacy abilities of children aged 5-6 years was included in the high category